The cannabinoid receptor CB1 interacts with the WAVE1 complex and plays a role in actin dynamics and structural plasticity in neurons - Njoo, Christian; Agarwal, Nitin; Kuner, Rohini (PLoS biology, 2015)
The molecular composition of the cannabinoid type 1 (CB1) receptor complex beyond the classical G-protein signaling components is not known. Using proteomics on mouse cortex in vivo, we pulled down proteins interacting with CB1 in neurons and show that the CB1 receptor assembles with multiple members of the WAVE1 complex and the RhoGTPase Rac1 and modulates their activity. Activation levels of CB1 receptor directly impacted on actin polymerization and stability via WAVE1 in growth cones of developing neurons, leading to their collapse, as well as in synaptic spines of mature neurons, leading to their retraction. In adult mice, CB1 receptor agonists attenuated activity-dependent remodeling of dendritic spines in spinal cord neurons in vivo and suppressed inflammatory pain by regulating the WAVE1 complex. This study reports novel signaling mechanisms for cannabinoidergic modulation of the nervous system and demonstrates a previously unreported role for the WAVE1 complex in therapeutic applications of cannabinoids.
Gesehen am 21.08.2020